การวิเคราะห์วิธีการพัฒนาตนเอง ของครูผู้สอนในสถาบันกวดวิชาในเขตพื้นที่กรุงเทพมหานคร - ธนภัทรศรีกุล สลิลา; สุดรุ่ง จุไรรัตน์ (An Online Journal of Education, 2018)
This research aimed to analyze a self-development method of teachers in tutorial institutes in Bangkok. The populations were 6,285 tutors from tutorial institutes in Bangkok. There were 30 sample of teachers in tutorial institutes were drawn from the total population, using a purposive sampling method. The samplings were selected by their popularity with learners or their expertise as a lecturer in other institutes or educational projects. The research instrument used was a structured-interview. The statistical analysis used was a content analysis. The findings of this research were as follows : Self-reflection. The motivation of tutors. The components of this success. The strengths of the tutors and their areas of development as a tutor. Goal. Tutors planned for own professional development. Practice for self-development : Tutors read textbooks. They also tried to apply new teaching techniques. Moreover, tutors sought a training or joined the workshops, seminars, educational field trip of various organizations, learned from the educational specialists, or professors, or peers to elevate their knowledge and teaching techniques. In addition, tutors had time management and reinforcement for themselves. Self-evaluation: The tutors used exam’s results as one of the evidence of goal’s achievement.